EVOLUTION OF RELIGIOUS CAPACITY IN THE GENUS HOMO: ORIGINS AND BUILDING BLOCKS: with Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Origins and Building Blocks"; Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Cognitive Time Sequence"; and Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Trait Complexity in Action through Compassion.". Issue 1 (12th February 2018) - Rappaport, Margaret Boone; Corbally, Christopher
Abstract: The large, ancient ape population of the Miocene reached across Eurasia and down into Africa. From this genetically diverse group, the chimpanzees, bonobos, gorillas, and humans evolved from populations of successively reduced size. Using the findings of genomics, population genetics, cognitive science, neuroscience, and archaeology, the authors construct a theoretical framework of evolutionary innovations without which religious capacity could not have emerged as it did. They begin with primate sociality and strength from a basic ape model, and then explore how the human line came to be the most adaptive and flexible of all, while coming from populations with reduced genetic variability. Their analysis then delves into the importance of neurological plasticity and a lengthening developmental trajectory, and points to their following article and the last building block: the expansion of the parietal areas, which allowed visuospatial reckoning, and imagined spaces and beings essential to human theologies. Approximate times for the major cognitive building blocks of religious capacity are given.